Insider Trading, Equity Issues, and CEO Turnover in Firms Subject to Securities Class Action - Niehaus, Greg; Roth, Greg (Financial management, 1999)
In the typical securities class action (SCA), firms and their managers are sued for securities law violations by shareholders who allege that managers fraudulently withheld negative information or published misleading information during a period known as the "class period." We examine insider selling and seasoned equity issues during this period to investigate whether managers have an unusual incentive to delay disclosure of negative information. We also examine whether firms that settle SCAs experience an abnormal level of CEO turnover, which would suggest that some suits have merit and that these suits provide a deterrent.